Dynamic Impact of Transfusion Ratios on Outcomes in Severely Injured Patients: Targeted Machine Learning Analysis of the PROPPR Randomized Clinical Trial - Nguyen, Minh (J Trauma Acute Care Surg, 2020)
BACKGROUND: Massive transfusion protocols to treat post-injury hemorrhage are based on pre-defined blood product transfusion ratios followed by goal-directed transfusion based on patient’s clinical evolution. However, it remains unclear how these transfusion ratios impact patient outcomes over time from injury. METHODS: The Pragmatic, Randomized Optimal Platelet and Plasma Ratios (PROPPR) is a phase 3, randomized controlled trial, across 12 level-I trauma centers in North America. From 2012 to 2013, 680 severely injured patients required massive transfusion. We used semi-parametric machine learning techniques and causal inference methods to augment the intent-to-treat analysis of PROPPR, estimating the dynamic relationship between transfusion ratios and outcomes: mortality and hemostasis at different time-points during the first 24 hours after admission. RESULTS: In the intention-to-treat analysis, the 1:1:1 group tended to have decreased mortality, but with no statistical significance. For patients in whom hemostasis took longer than 2 hours, the 1:1:1 ratio was associated with a higher probability of hemostasis, statistically significant from the 4(th) hour on. In the per-protocol, actual-transfusion-ratios-received analysis, during four successive time intervals, no significant association was found between the actual ratios and mortality. When comparing patient groups who received both high plasma:PRBC and high platelet:PRBC ratios to the group of low ratios in both, the relative risk of achieving hemostasis was 2.49 (95% CI = 1.19–5.22) during the 3(rd) hour after admission, suggesting a significant beneficial impact of higher transfusion ratios of plasma and platelets on hemostasis. CONCLUSIONS: Our results suggest that the impact of transfusion ratios on hemostasis is dynamic. Overall, the transfusion ratios had no significant impact on mortality over time. However, receiving higher ratios of platelets and plasma relative to red blood cells hastens hemostasis in subjects who have yet to achieve hemostasis within 3 hours after hospital admission.